Management of lung cancer in South East Scotland. Issue 6 (June 1996) - Fergusson, R J; Gregor, A; Dodds, R; Kerr, G
Abstract : BACKGROUND: There are few reports which describe the management of unselected groups of patients with lung cancer. This study was undertaken to audit prospectively the presentation, diagnosis, management, and outcome of patients presenting with lung cancer in South East Scotland. METHODS: Data were recorded on all patients with newly diagnosed lung cancer who presented to a multidisciplinary group of clinicians over a 12 month period. Subsequent follow up data on treatment and survival were collected. RESULTS: Six hundred and twenty two patients were registered, 80% of whom were referred from primary care. There was a considerable variation in the length of history, but the diagnosis was rapidly made after referral (87% within two weeks). In 82% of patients the pathological examination was positive; 70% were treated with palliative intent. Only 36% of patients who underwent surgery had computed tomographic scanning and 55% had sampling of mediastinal nodes. A wide variety of regimens was used for treatment with radiotherapy and chemotherapy, and follow up data were difficult to obtain in these patients. Survival was poor in all patients treated with palliative intent. CONCLUSIONS: This audit confirms the importance of previously noted prognostic factors. Significant variation in referral practice, diagnostic and management evaluation has been shown. The data serve as a useful background for the formation of local management guidelines.